A rare case of peritoneo-cutaneous fistula after cesarean section - Rana, Anshul; Mohindroo, Neha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Peritoneo-cutaneous fistula is usually a rare but known entity. Such a case has not been reported after cesarean sections. A 26-year female presented to our clinic in May 2019 with persistent sero-purulent discharge from sinus over abdominal skin. The patient had previously undergone a cesarean section in April 2018 for premature rupture of membranes and non-progress of labour. The surgery and puerperal period were uneventful. The patient presented with document high-grade fever in June 2018. In August 2018, a localized painful swelling was noted by the patient herself over the abdomen, contrast-enhanced computed tomography, which suggested 6.3×3.9×3 cm collection in the right adnexal region and a fistulous tract communicating with abdominal skin. For the same she underwent surgery, wide local excision of the fistulous tract around elliptical skin incision was done. The development of delayed peritoneo-cutaneous fistula has been seen as a complication of difficult cholecystectomy.